2006
DOI: 10.1021/jf0622432
|View full text |Cite
|
Sign up to set email alerts
|

High-Amylose Corn Exhibits Better Antioxidant Activity than Typical and Waxy Genotypes

Abstract: The consumption of fruits, vegetables, and whole grains rich in antioxidative phytochemicals is associated with a reduced risk of chronic diseases such as cancer, coronary heart disease, diabetes, Alzheimer's disease, cataract, and aged-related functional decline. For example, phenolic acids are among the main antioxidative phytochemicals in grains that have been shown to be beneficial to human health. Corn (Zea mays L.) is a major staple food in several parts of the world; thus, the antioxidant activity of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 38 publications
6
35
0
Order By: Relevance
“…Whole and unpolished grain of hulless barley consist mainly of starchy endosperm, and hence the ratio of amylose and amylopectin content can effect not only the quality of obtained baking products but also the antioxidant activity. For example, it has been shown that high-amylose corn has better antioxidant activity than typical corn genotypes (Li et al, 2007). In our study, the only genotype 'PR 3440' with waxy or high-amylopectin endosperm also showed higher radical scavenging activity and total phenolic content.…”
Section: Discussionsupporting
confidence: 47%
“…Whole and unpolished grain of hulless barley consist mainly of starchy endosperm, and hence the ratio of amylose and amylopectin content can effect not only the quality of obtained baking products but also the antioxidant activity. For example, it has been shown that high-amylose corn has better antioxidant activity than typical corn genotypes (Li et al, 2007). In our study, the only genotype 'PR 3440' with waxy or high-amylopectin endosperm also showed higher radical scavenging activity and total phenolic content.…”
Section: Discussionsupporting
confidence: 47%
“…[9] The reagent of Folin-Ciocalteu consists of a mixture of acid phosphotungstic and phosphomolybdic acid. During oxidation, it is reduced to a mixture of blue oxide.…”
Section: Determination Of Total Polyphenolsmentioning
confidence: 99%
“…Fruit samples were subjected to alkaline hydrolysis for determination of their phenolic acid composition by HPLC according to our previous method with some modification [16]. The hydrolysis procedure was as follows.…”
Section: Sample Preparationmentioning
confidence: 99%